Milton’s Angels: The Early Modern Imagination. By Joad Raymond - Spurr, John (The journal of theological studies, 2011)
‘What surmounts the reach / Of human sense, I shall delineate so, / By likening spiritual to corporeal forms’, says the angel Raphael in John Milton’s epic poem Paradise Lost. Although this is a poem about the Fall of Man, most of the agents and events that figure in its narrative are beyond the realm of human experience. Angels narrate the drama and recount the angelic war in heaven that precedes the creation itself: Raphael, the ‘heavenly guest, ethereal messenger’, sits down with Adam to describe creation; Michael, having driven the sinful pair from Eden, vouchsafes Adam a vision of fallen mankind’s future; while Satan, the fallen angel, can, of course, be said to drive much of the action of the poem.